Convergence Comparison of two Schemes for Common Fixed Points with an Application - Abed, Salwa Salman; Mohamed Hasan, Zahra Mahmood (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2019)
Some cases of common fixed point theory for classes of generalized nonexpansive maps are studied. Also, we show that the Picard-Mann scheme can be employed to approximate the unique solution of a mixed-type Volterra-Fredholm functional nonlinear integral equation.